Stylistyczne aspekty dyskursu feministycznego ( Wokół znaczenia terminu dyskurs w tekstologii lingwistycznej) - Witosz, Bożena (Stylistyka, 2008)
The author presents the analysis of a feminist discourse from the perspective of contemporary stylistics. The discourse is treated, according to the M. Foucault’s concept, as a type of communicative practice, institutionally and culturally conditioned. The writer emphasizes that in the description of style, the cultural context and the place of feminist discourse in relation to other varieties of communication have to be considered. A feminist discourse is an open category that is dispersed and expansive, with numerous sub varieties, which decide about its dynamics and multiplicity of styles. The author differentiates between a women’s discourse and a feminist discourse. The indicator of that difference is the attitude of the subject. In a feminist discourse the subject is deeply involved ideologically. The presented description of the style includes: the selection of the expression genres, viewpoints of the subject, the vision of the world, various profiles of a woman and femininity, characteristic range of values (difference, openness, body, maternity, care...), their contextual valorization and the complex of metaphors. In conclusion the author states that the characteristics of a feminine discourse are not linguistic features but the sphere of values, ideology, attitudes and strategies of the subject.